2005
DOI: 10.1002/hep.20507
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of hepatitis C virus-specific T-cell-mediated immunity after liver transplantation

Abstract: Hepatitis C virus (HCV)-related liver failure is the leading indication for liver transplantation worldwide. After transplantation, virological recurrence is the rule, but the spectrum of histological injury is wide, ranging from the development of allograft cirrhosis within a few years to minimal hepatitis despite long-term follow-up. The immunological correlates of this variable natural history are poorly understood. Here, we studied the kinetics of the cellular immune responses, viral replication, and allog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 32 publications
4
49
0
Order By: Relevance
“…16 We coated a total of 96-well nitrocellulose-backed plates (MAHA S4510; Millipore, Bedford, MA) as recommended by the manufacturer with 10 g/mL capture mouse anti-IFN-␥ (1-D1K; Mabtech AB, Nacka, Sweden) overnight at room temperature. We then washed plates 3 times with PBS/0.05% Tween 20 (Sigma), and blocked them with RPMI/10% human serum for 1 hour at room temperature.…”
Section: Ifn-␥ Elispot Assaymentioning
confidence: 99%
“…16 We coated a total of 96-well nitrocellulose-backed plates (MAHA S4510; Millipore, Bedford, MA) as recommended by the manufacturer with 10 g/mL capture mouse anti-IFN-␥ (1-D1K; Mabtech AB, Nacka, Sweden) overnight at room temperature. We then washed plates 3 times with PBS/0.05% Tween 20 (Sigma), and blocked them with RPMI/10% human serum for 1 hour at room temperature.…”
Section: Ifn-␥ Elispot Assaymentioning
confidence: 99%
“…Reconstitution of CD8ϩ T-cell responses to HCV antigens has been described in FCH cases after response to antiviral therapy. 2 Such reconstitution is not seen in patients unresponsive to treatment. Antiviral therapy leading to control of viral load and cytopathic damage probably allowed time for immune reconstitution.…”
Section: To the Editorsmentioning
confidence: 99%
“…Patients with mild recurrence presented higher intersample GD and, a trend towards a greater number of Aa fixations, as compared with patients undergoing severe recurrence. Although multiple variables (such as host-related factors and the genetic back-ground of the graft) may influence the severity of the recurrence, previous studies have shown that severe hepatitis recurrence after LT occurred in patients with impaired HCV-specific T-cell responses, whereas the histological and clinical outcomes were better in those with efficient T-cell response (42,43). Therefore, the increased degree of genetic diversification of the NS5b region in patients with mild recurrence might be a consequence of a more prominent immunological pressure in this group of patients.…”
Section: Discussionmentioning
confidence: 99%